2021
DOI: 10.1021/acs.energyfuels.1c03807
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Amine-Based Ternary Deep Eutectic Solvents for Efficient, Rapid, and Reversible SO2 Absorption

Abstract: Effective and reversible absorption of sulfur dioxide (SO 2 ) with commercially available and easily prepared absorbents now has drawn increasing concentration. In this work, a series of amine-based ternary deep eutectic solvents (DESs) composed of diethylenetriamine (DETA), acetamide (AA), and ethylene glycol (EG) were prepared to study the SO 2 absorption performance. Results demonstrate that these obtained ternary DESs not only exhibit a rapid absorption rate but also present desirable absorption capacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…This may be due to the higher charge density of NMP over 2-pyr, or the higher alkalinity of Eim over Im, which leads to the stronger interaction with SO 2 . 18 Nevertheless, the HBD component (2-pyr or Im) also has good SO 2 absorption capacity to pair with its HBA homologue (NMP or Eim), so that the HPL can be treated as a SO 2 absorbent of low volatility. Even though the SO 2 loading (0.63 g g À1 ) in NMP-2-Pyr (1 : 1) is slightly lower than that in pure NMP (0.68 g g À1 ) at 313.2 K and 1 bar (Fig.…”
mentioning
confidence: 99%
“…This may be due to the higher charge density of NMP over 2-pyr, or the higher alkalinity of Eim over Im, which leads to the stronger interaction with SO 2 . 18 Nevertheless, the HBD component (2-pyr or Im) also has good SO 2 absorption capacity to pair with its HBA homologue (NMP or Eim), so that the HPL can be treated as a SO 2 absorbent of low volatility. Even though the SO 2 loading (0.63 g g À1 ) in NMP-2-Pyr (1 : 1) is slightly lower than that in pure NMP (0.68 g g À1 ) at 313.2 K and 1 bar (Fig.…”
mentioning
confidence: 99%
“…As shown in Figure , compared with the FT-IR spectra of the virgin DESs, new peaks presented at 953 and 1722 cm –1 could be ascribed to S–O stretch vibrations and the interaction of N of the 4-Op with SO 2 . ,, The above result indicated that there was chemical interactions between 4-Op/BmimCl (1:2) and SO 2 . The typical characteristic peaks appeared at 536, 1128, and 1310 cm –1 after DESs saturated with SO 2 , which could be ascribed to the bending vibration of SO 2 ,, and the symmetrical and asymmetrical stretching vibration of SO, , respectively. Generally, the symmetrical and asymmetrical stretching vibration of SO 2 were observed at 1145 and 1344 cm –1 in CCl 4 , respectively .…”
Section: Resultsmentioning
confidence: 97%
“…Fig. S2 † shows the 13 C NMR of the incomplete reaction products with imidazole hydrochloride and styrene oxide. Obviously, styrene oxide is not completely converted and its signal is very prominent.…”
Section: Resultsmentioning
confidence: 99%
“…22 Fig. 3a presents the 13 C NMR of the mixed mother liquor from Scheme 1f. It is found that there is no obvious styrene oxide that can be detected.…”
Section: Resultsmentioning
confidence: 99%